The Interfaith Youth Campaign For A Culture Of Peace (A Case Study Of An Interfaith Youth “Pelita” From Cirebon) - Rifa’i, Akhmad; Alimah, Alimah (Jurnal Komunikasi Islam, 2015)
Violent conflict in the name of religion has been causing anxiety amongst societies, including the youth in Cirebon and surrounding areas. Through the efforts of peace-building, a number of youth of different faiths, beliefs and cultures, has declared as an Interfaith Youth Organization or popularly known as “Pelita”. They campaign culture of peace as one of the peace-building efforts with a variety of activities. Pelita is not only utilizing conventional campaign, but also modern campaign by utilizing mass media, social media, and blogs. The conventional campaign hold through a variety of events or activities considered are the best able to persuade the society such as roadshow and peaceful demonstration. Pelita's campaign strategy is also incorporating elements of local wisdom. By using campaign culture of peace, Pelita has been able to encourage the appreciation, participation and minimize the destructive elements of solidarity and community integration.